2021
DOI: 10.1038/s41592-020-01052-9
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the protein composition of whole nucleosomes with Nuc-MS

Abstract: Nuc-MS characterizes histone modifications and variants directly from intact endogenous nucleosomes. Preserving whole nucleosome particles enables precise interrogation of their protein content, as for H3.3-containing nucleosomes which had 6fold co-enrichment of variant H2A.Z over bulk chromatin. Nuc-MS, validated by ChIPseq, showed co-occurrence of oncogenic H3.3K27M with euchromatic marks (e.g., H4K16ac and >15-fold enrichment of H3K79me2). By capturing the entire epigenetic landscape, Nuc-MS provides a new,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…We identified upregulation of H4K16ac as one of the most prominent effects of H3-K27M expression, similar to the well-established upregulation of H3K27ac 29 . Schachner et al recently applied mass spectrometry to intact nucleosomes and showed high levels of H4K16ac on H3-K27M-mutant nucleosomes 55 , supporting a cis effect of the mutation on this specific H4 acetylation. The global increase observed in our data strongly suggests a trans effect as well, similar to H3K27ac.…”
Section: Discussionmentioning
confidence: 97%
“…We identified upregulation of H4K16ac as one of the most prominent effects of H3-K27M expression, similar to the well-established upregulation of H3K27ac 29 . Schachner et al recently applied mass spectrometry to intact nucleosomes and showed high levels of H4K16ac on H3-K27M-mutant nucleosomes 55 , supporting a cis effect of the mutation on this specific H4 acetylation. The global increase observed in our data strongly suggests a trans effect as well, similar to H3K27ac.…”
Section: Discussionmentioning
confidence: 97%
“…This allows the analysis of protein complexes and their PTMs, thereby enabling the study of inter-protein PTM crosstalk ( 65 ). Indeed, a recent study applied native top-down mass spectrometry to quantify the relative abundance of histone isoforms and their respective PTM-proteoforms from endogenous nucleosome preparations in a single mass spectrum ( 66 ). While limited by low throughput, low proteome coverage, and protein-specific sample preparation considerations, top-down methods are highly complementary to bottom-up approaches and allow for complex patterns of intra- and inter-protein PTM co-occurrence to be measured for proteins and complexes of interest.…”
Section: Proteomic Methods To Identify Ptm Crosstalkmentioning
confidence: 99%
“…Cracking the H2A.Z nucleosome code and deciphering H2A.Z nucleosome dynamics during specific molecular processes is key to further understanding H2A.Z differential functions. With implementation of single-molecule imaging in living cells [113], as well as Nuc-MS to study nucleosomes in their native form [36], MNase-X-ChIP [22] to interrogate unwrapping nucleosomes, and ChIP-re-ChIP [114] to investigate histone co-occurrence in the chromatin, we envision that studies in the next 5 years will detail the dynamics and composition of H2A.Z nucleosomes during transcription and molecular processes, such as replication and DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed method, nucleosome mass spectrometry (Nuc-MS), that captures the protein composition of synthetic or endogenous nucleosomes in their native form, confirmed that H3.3 nucleosomes have a sixfold enrichment of H2A.Z over bulk chromatin [36]. According to Nuc-MS, around 13% of H3.3 nucleosomes also contain H2A.Z, in line with the 20% overlap between H2A.Z and H3.3 ChIP-seq peaks found at promoter and intronic regions.…”
Section: Trends In Geneticsmentioning
confidence: 98%